Carvedilol Inhibits the Exogenous NADH Dehydrogenase in Rat Heart Mitochondria - Oliveira, Paulo J. (2000)
There are several reports on the oxidation of external NADH by an exogenous NADH dehydrogenase in the outer leaflet of the inner membrane of rat heart mitochondria. Until now, however, little was known about its physiological role in cellular metabolism. The present work shows that carvedilol ({1-[carbazolyl-(4)-oxy]-3-[2-methoxyphenoxyethyl)amino]-pro- panol-(2)}) is a specific inhibitor of an exogenous NADH dehydrogenase in rat heart mitochondria. Carvedilol does not affect oxygen consumption linked to the oxidation of succinate and internal NADH. It is also demonstrated that the inhibition of exogenous NADH dehydrogenase by carvedilol is accompanied by the inhibition of alkalinization of the external medium. In contrast to the addition of glutamate/malate or succinate, exogenous NADH does not generate a membrane potential in rat heart mitochondria, as observed with a TPP+ electrode. It is also demonstrated that the oxygen consumption linked to NADH oxidation is not due to permeabilized mitochondria, but to actual oxidase activity in the inner membrane. The enzyme has a Km for NADH of 13 [mu]M. Carvedilol is a noncompetitive inhibitor of this external NADH dehydrogenase with a Ki of 15 [mu]M. Carvedilol is the first inhibitor described to this organospecific enzyme. Since this enzyme was demonstrated to play a key role in the cardiotoxicity of anticancer drugs of the anthracycline family (e.g., adriamycin), we may suggest that the administration of carvedilol to tumor patients treated with adriamycin might be of great help in the prevention of the cardioselective toxicity of this antibiotic.